Analysis of the Constitutional Court Decision on Election Campaigns at Educational Institutions from the Perspective of the Purpose of Law - Radjak, Sarmila; I. Rahim, Erman; Ahmad, Ahmad (Estudiante Law Journal, 2025)
The conduct of elections in Indonesia as a manifestation of people's sovereignty requires guarantees of justice, legal certainty, and the neutrality of public institutions. The Constitutional Court Decision Number 65/PUU-XXI/2023, which permits election campaigns at educational institutions under certain conditions such as obtaining permission and appearing without campaign attributes has sparked significant debate. This study aims to analyze the court's legal considerations in this decision and evaluate it from the perspective of Gustav Radbruch’s theory of the purpose of law, which encompasses justice, legal certainty, and utility. The research employs a normative juridical method, utilizing statutory and conceptual approaches to analyze the Constitutional Court’s decision, the Election Law, and its implementing regulations. The findings indicate that the decision has established legal certainty by resolving the ambiguity and contradiction between the main provision and the explanatory note of Article 280 paragraph (1) letter h of Law Number 7 of 2017. It also generates societal benefit by opening political education opportunities for young voters, in line with Article 267 paragraph (1) of the Election Law. However, from the standpoint of substantive justice, the ruling risks creating unequal access for legislative candidates with only secondary education and may compromise the neutrality of educational institutions and civil servants. Therefore, while the decision achieves legal certainty and utility, it falls short in fully realizing substantive justice. Strict supervision and further regulatory refinement are needed to safeguard the integrity of democracy